2014
DOI: 10.1002/kin.20868
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence Kinetic Studies of the Reaction of O(3P) with CHI3 and C2H5I and the 298 K Reaction of OH(X2Π) with CHI3

Abstract: A flash photolysis–resonance fluorescence technique was used to investigate the kinetics of the OH(X2Π) radical and O(3P) atom‐initiated reactions with CHI3 and the kinetics of the O(3P) atom‐initiated reaction with C2H5I. The reactions of the O(3P) atom with CHI3 and C2H5I were studied over the temperature range of 296 to 373 K in 14 Torr of helium, and the reaction of the OH (X2Π) radical with CHI3 was studied at T = 298 K in 186 Torr of helium. The experiments involved time‐resolved resonance fluorescence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Similar theoretical results can be also found in the reaction of C 2 H 5 I with a Cl atom 45 and for other alkyl iodides reactions with O( 3 P) and OH radicals. 19,47,48 Fig. 4a and b show the temperature dependence of the branching ratios for the reactions of CH 3 I and C 2 H 5 I with a NO 3 radical, respectively.…”
Section: Rate Constant Calculations and Branching Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar theoretical results can be also found in the reaction of C 2 H 5 I with a Cl atom 45 and for other alkyl iodides reactions with O( 3 P) and OH radicals. 19,47,48 Fig. 4a and b show the temperature dependence of the branching ratios for the reactions of CH 3 I and C 2 H 5 I with a NO 3 radical, respectively.…”
Section: Rate Constant Calculations and Branching Ratiosmentioning
confidence: 99%
“…17 In the last few years, attention has focused on the NO 3 nighttime reactivity in urban zones with a series of hydrogen compounds. [18][19][20][21][22] Herein, we focus on the important iodine cycle reactions, namely CH 3 I and C 2 H 5 I with NO 3 radicals. The reactions can proceed via seven reaction channels, including Habstraction ((R1a, R2a), (R1b), (R2b and R3b)) and displacement ((R3a) and (R4b)), e.g., The reactions of NO 3 with CH 3 I and C 2 H 5 I were reported by Nakano et al 9,12 through the cavity ring-down spectroscopy method.…”
Section: Introductionmentioning
confidence: 99%
“…The gas phase CH 3 I was introduced into the chamber using the gas saturation method first developed by Regnault in 1845 [35]; one of the oldest and most versatile ways of studying gasliquid equilibria involving low vapor pressure compounds. Further, the gas saturation method used in this work is similar to the one employed in a number of other studies of atmospheric interest [36,37,38,39] where precise reactant concentrations of volatile or semi-volatile compounds needed to be known. Its operation principle and the calculation of the concentration of CH 3 I leaving the saturation system have been presented in detail elsewhere [40].…”
Section: Reactantsmentioning
confidence: 99%
“…Subsequently, Zhang et al [19] widened the reaction temperature interval to T = 297-372 K and explored the temperature-dependent effects of the rate coefficients. In addition, Zhang et al [23] measured the kinetic parameters of the reactions of * OH and O( 3 P) atoms with CHI 3 and C 2 H 5 I in the temperature range T = 296-373 K using flash photolysis resonance fluorescence technique. A theoretical study was reported by Marshall et al [24] on the H-abstraction and I-abstraction pathways for the reaction of CH 3 I with * OH at the MP2/6-31G(d) level and found that the H-abstraction reaction outperformed the I-abstraction reaction.…”
Section: Introductionmentioning
confidence: 99%